PREJUDICE TOWARDS AFRICAN-AMERICAN IN SMALL GREAT THINGS NOVEL - Syamsudin, Tiara Ananda; Zamruddin, Mardliya Pratiwi; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
Prejudice is a negative assumption towards others which is not certain to be right or wrong yet. One of the problems of prejudice that still exists in the modern era is prejudice against African Americans. This research aimed to reveal the kinds of prejudice experienced by African-Americans and the responses of African-American characters as the victims of prejudice. To conduct this research, the researcher used qualitative methodology. The data in this research were taken in the form of narrations and dialogues in Small Great Things (2016) novel written by Jodi Picoult which related to the negative actions of prejudice experienced by African-American characters and their responses to the prejudices that suitable with prejudice theory by Gordon Allport and the response to prejudice theory by Simpson and Yinger. The results showed that African-American characters in Small Great Things novel experience four kinds of prejudice, namely: antilocution, avoidance, discrimination and physical attack. Furthermore, the result also showed how African-American characters responded to the prejudices that they experienced, namely: aggression, acceptance and reformism. Therefore, the researcher concluded that prejudice based on individual beliefs can make someone behave negatively toward others and sometimes it can be manifested through hostile actions.